Keterlibatan Masyarakat Sipil dalam Pemilihan Umum: Peran Muhammadiyah pada Pemilihan Presiden 2019 - Walinegoro, Bhakti Gusti; Widodo, Bambang Eka Cahya (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2021)
The 2019 Presidential Election was a big challenge for Muhammadiyah. Apart from having to play its role as a civil society, Muhammadiyah faced an internal elite fragmentation and social conflicts that resulted from the 2019 Presidential Election. The purpose of this article is to analyze the roles played, elite fragmentation, and conflict resolution pursued by Muhammadiyah in the 2019 Presidential Election. The method used in this research was a qualitative case study. The results of this study indicate that in the 2019 Presidential Election, Muhammadiyah played its roles as a civil society including providing public services, being substitute for the government and keeping social-political balance. Moreover, Muhammadiyah attempted to manage the elite fragmentation within Muhammadiyah during the 2019 Presidential Election by separating its members’ personal political choices from its formal organisational political stance of neutrality. This article concludes that in the 2019 Presidential Election, Muhammadiyah emphasized its position as a power of civil society in Indonesia and strengthened its commitment not to engage in practical politics.